2019
DOI: 10.1159/000501477
|View full text |Cite
|
Sign up to set email alerts
|

Association between High Levels of Circulating Chemerin and Colorectal Adenoma in Men

Abstract: Background: Obesity and metabolic syndrome are considered the risk factors of colorectal adenoma (CRA) and colorectal cancer (CRC). Chemerin is a novel adipocytokine associated with the development of gastric cancer, esophageal cancer, hepatocellular carcinoma, and CRC. However, the relationship between chemerin levels and CRA remains unclear. Objective: This study is aimed at investigating the association between serum chemerin levels and the development of CRA. Methods: We conducted a total colonoscopy-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Aging and reduced food intake due to CRC development may have altered the weight of patients with CRC, particularly in the advanced stage. Nevertheless, glucose intolerance and insulin resistance were observed in patients with CRC, which is consistent with previous reports [4][5][6][7][8][9][10][11][12] that metabolic abnormalities associated with Figure 5 Comparison of the genera between obese and nonobese patients with colorectal cancer (CRC). In the obese patients with CRC, the genus Enterococcus (P = 0.04) was significantly lower, and the genera Polaribacter (P = 0.03) and Capnocytophaga (P = 0.03) were significantly higher than in the nonobese patients with CRC.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Aging and reduced food intake due to CRC development may have altered the weight of patients with CRC, particularly in the advanced stage. Nevertheless, glucose intolerance and insulin resistance were observed in patients with CRC, which is consistent with previous reports [4][5][6][7][8][9][10][11][12] that metabolic abnormalities associated with Figure 5 Comparison of the genera between obese and nonobese patients with colorectal cancer (CRC). In the obese patients with CRC, the genus Enterococcus (P = 0.04) was significantly lower, and the genera Polaribacter (P = 0.03) and Capnocytophaga (P = 0.03) were significantly higher than in the nonobese patients with CRC.…”
Section: Discussionsupporting
confidence: 88%
“…3 The underlying mechanisms linking obesity to CRC remain a matter of debate; however, metabolic syndrome, insulin resistance, and alterations in adipocytokine concentrations appear to be of great importance. 4 The authors of this study previously demonstrated that visceral fat obesity and metabolic syndrome, insulin resistance following hyperinsulinemia, 5 impaired secretion of adipocytokine [6][7][8] or incretin, 9,10 and systemic low chronic inflammation 11,12 contribute to the development of CRC or colorectal adenoma, which is a well-known precancerous lesion of CRC.…”
Section: Introductionmentioning
confidence: 91%
“…Elevated circulating chemerin in CRC patients was described in recent studies [7,9]. In patients with adenomas serum chemerin was nearly 50% higher than in healthy controls [14]. Chemerin concentration of CRC patients was about 15% increased in one CRC cohort whereas the second analysis reported a more than four-fold induction compared to healthy controls [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…In colon cancer patients, chemerin was increased though it was not associated with TNM classification [9]. Sytemic chemerin was further positively related to the number of adenomas in patients with colorectal adenomas [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation